Environmental SARS-CoV-2 contamination in hospital rooms of patients with acute COVID-19. (August 2022) - Nagle, S.; Tandjaoui-Lambiotte, Y.; Boubaya, M.; Athenaïs, G.; Alloui, C.; Bloch-Queyrat, C.; Carbonnelle, E.; Brichler, S.; Cohen, Y.; Zahar, J-R.; Delagrèverie, H.
Summary: Objective: Data on the transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) remain conflicting. Airborne transmission is still debated. However, hospital risk control requires better understanding of the different modes of transmission. This study aimed to evaluate the frequency of, and factors associated with, environmental air and surface contamination in the rooms of patients with coronavirus disease 2019 in the acute phase of the disease. Methods: Sixty-five consecutive patients were included in this study. For each patient, seven room surfaces, air 1 m and 3 m from the patient's head, the inner surface of the patient's mask, and the outer surface of healthcare workers' (HCW) masks were sampled. Environmental contamination was assessed by quantitative reverse transcription polymerase chain reaction (RT-qPCR) for SARS-CoV-2 RNA on surfaces, air and masks. A viral isolation test was performed on Vero cells for samples with an RT-qPCR cycle threshold (Ct) ≤37. Results: SARS-CoV-2 RNA was detected by RT-qPCR in 34%, 12%, 50% and 10% of surface, air, patient mask and HCW mask samples, respectively. Infectious virus was isolated in culture from two samples among the 85 positive samples with Ct ≤37. On multi-variate analysis, only a positive result for SARS-CoV-2 RT-qPCR for patients' face masks was found to be significantly associated with surface contamination (odds ratio 5.79, 95% confidence interval 1.31–25.67; P =0.025). Conclusion: This study found that surface contamination by SARS-CoV-2 was more common than air and mask contamination. However, viable virus was rare. The inner surface of a patient's mask could be used as a marker to identify those at higher risk of contamination.